Determinants of Disclosure of Islamic Social Reporting (ISR) On Financial Performance in Islamic Banking - Hilwa Fitri Millenia; Asyari Hasan (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of Islamic Social Reporting (ISR) disclosure on financial performance. The dependent variable used in this study is financial performance as measured by Return on Assets (ROA). The independent variable in this study is Islamic Social Reporting (ISR). The population in this study is the Islamic banking industry registered with the Financial Services Authority (OJK) for the period 2011-2020. The sample in this study were 8 Islamic banks selected using purposive sampling method. This study uses linear regression analysis of panel data as a data analysis tool. The statistical tool used is Eviews 9. The results show that the disclosure of Islamic social reporting has a significant positive effect on return on assets (ROA) with a prob value0.0102or less than 0.05. So that ISR can be used to predict ROA with a positive coefficient direction, meaning that if ISR increases, ROA will increase, which means that financial performance will increase.